A short review on polymeric materials concerning degradable polymers - N., Sazali; H., Ibrahim; A. S., Jamaludin; M. A., Mohamed; W. N. W., Salleh; M. N. Z., Abidin (IOP Publishing, 2020)
The demand for cutting-edge functional materials has been increasing since the decade. Polymeric materials usage in the past decade contributes to its commercial accomplishment, thus encouraging more groundbreaking research-based activities. Although this news is promising for polymer-related industries, the fast consumption rate of these materials throughout the world will seriously harm the environment through the accumulation of waste materials sourced primarily from by-products, faulty products or municipal from various agricultural farms and industries with disposal difficulties. Wide usage of polymeric materials is due to their ease of processing, light weight and relatively low manufacturing cost. Various advancements were made over the years in developing polymeric materials of high performance. Structure and ionic bonds of polymeric and biomaterials are the reason behind their physical and chemical properties. However, their usage is limited due to expensive manufacturing cost and difficulty in shaping and processing them.